Bah, humduck! : a looney tunes Christmas - Molieri, Frank; DeLaurentis, Ray.; Visser, Charles; Alaskey, Joe.; Bergen, Bob.; West, Billy; Foray, June.; LaMarche, Maurice, 1958-; Cummings, Jim, 1952-; Strong, Tara, 1973-; Goodwin, Gordon L.; Warner Bros. Animation; et al. (Burbank, CA : Warner Home Video, 2006)
Follow the exploits of Daffy Duck, the Scrooge-like proprietor of the Lucky Duck Mega-Mart. Daffy demands that his employees work on Christmas Day. It's up to Bugs Bunny and the ghosts of Christmas to save the day.
Special features: additional scenes; Bah, Humbduck! The Lucky Duck, Dilemma menu Challenge; Hah, Humduck! music video.
Editor, Rob DeSales ; music by Gordon Goodwin ; production manager, Helen Smitheman.
Starring the voice talents of Joe Alaskey, Bob Bergen, Billy West, June Foray, Maurice LaMarche, Jim Cummings, and Tara Strong.
Rating: Not rated.
DVD, region 1, full screen presentation; Dolby Digital.
English (Dolby surround 5.1), French (Dolby surround stereo.), Spanish (Dolby surround stereo.); closed-captioned.
Keywords: Daffy Duck (Fictitious character) -- Juvenile drama; Christmas -- Juvenile drama; Ghosts -- Juvenile drama; Christmas films; Animated films; Children's films; Comedy films; Drama; Feature films; Juvenile works; Video recordings for the hearing impaired